Evaluation of a Dual Isolation Width Acquisition Method for Isobaric Labeling Ratio Decompression - Roumeliotis, Theodoros I. (J Proteome Res, 2018)
[Image: see text] Isobaric labeling is a highly precise approach for protein quantification. However, due to the isolation interference problem, isobaric tagging suffers from ratio underestimation at the MS2 level. The use of narrow isolation widths is a rational approach to alleviate the interference problem; however, this approach compromises proteome coverage. We reasoned that although a very narrow isolation window will result in loss of peptide fragment ions, the reporter ion signals will be retained for a significant portion of the spectra. On the basis of this assumption, we have designed a dual isolation width acquisition (DIWA) method, in which each precursor is first fragmented with HCD using a standard isolation width for peptide identification and preliminary quantification, followed by a second MS2 HCD scan using a much narrower isolation width for the acquisition of quantitative spectra with reduced interference. We leverage the quantification obtained by the “narrow” scans to build linear regression models and apply these to decompress the fold-changes measured at the “standard” scans. We evaluate the DIWA approach using a nested two species/gene knockout TMT-6plex experimental design and discuss the perspectives of this approach.